Axial stress versus strain responses of CFRP confined concrete containing electronic waste aggregates - Ullah, Saad; Qureshi, Muhammad Irshad; Saingam, Panumas; Hussain, Qudeer; Khan, Kaffayatullah; Yooprasertchai, Ekkachai (My University, 2023)
This research work investigates the axial stress versus strain responses of un-strengthened and carbon fiber reinforced polymer (CFRP) composites strengthened concrete specimens made with electronic waste coarse aggregates. For this purpose, 36 circular and non-circular 300 mm high concrete specimens constrained with CFRP sheets and partially replaced with E-waste coarse aggregates were prepared. The effect of cross-sectional geometry, 20% partial substitution of natural coarse aggregates with E-waste aggregates, corner effect of non-circular concrete specimens, confinement of specimens with CFRP sheets, and effect of the number of confinement sheets were also studied. In control concrete specimens, the coarse aggregates were 848 kg/m3 and E-waste aggregates were 212 kg/m3. The cement was 475 kg/m3 and fine aggregates were 655 kg/m3. Test results indicated that compressive strength is reduced by substituting natural coarse aggregates with E-waste aggregates. At the same time, compressive strength increased to 71%, 33%, and 25% for circular, square, and rectangular concrete specimens, respectively, by CFRP confinement. Whereas the axial strain increased to 1100%, 250%, and 133%, for circular, square, and rectangular concrete specimens, respectively, by CFRP confinement. CFRP sheets also enhanced the Poisson's ratio. Because of the greater confinement given by a double CFRP layer, it is more effective than a single layer. Furthermore, results also indicated that strength reduction in non-circular concrete specimens was greater than in circular concrete specimens for all studied cases. In the end, for theoretical calculations, strength and strain models for confined concrete suggested by different researchers were applied and compared with experimental results. In comparison to the experimental findings, theoretical data showed that most of the models were either on the higher or on the lower side, while only some model results matched well with the experimental data.